Advance Pricing Agreement for Preventing Transfer Pricing Disputes in International Trade Law - Nathan Thomas; Hafid Zakariya; Diajeng Lita Pratiwi (Fakultas Hukum Universitas Islam Indonesia, 2026)
Companies often engage in purchase and sale transactions with related parties. Some companies utilize such transactions as instruments in transfer pricing practices. Advance Pricing Agreement is a written agreement mechanism used to determine the arm’s length price for transactions between related parties. This study aims to analyze the implementation mechanism of the Advance Pricing Agreement in preventing transfer pricing disputes and to examine the challenges of its implementation from the perspective of international trade law. The author employs a normative juridical research method, using a statutory approach and a case study approach involving transfer pricing disputes such as PT Covestro Polymers Indonesia and Court Decision No. PUT 003777.15/2023/PP/M.XVIIIA (2024) in the case of PT VVF Indonesia vs the Directorate General of Taxes (DGT), which discusses the application of the Advance Pricing Agreement in resolving tax disputes. The findings indicate that the implementation of the Advance Pricing Agreement serves as a legal instrument capable of creating legal certainty, transparency, and efficiency in resolving potential transfer pricing disputes. Minister of Finance Regulation (PMK) No. 172/2023 strengthens the legal foundation for Advance Pricing Agreement implementation in Indonesia. However, several challenges remain in its practical application. Overall, the study concludes that the Advance Pricing Agreement functions as a legal solution to prevent transfer pricing disputes and reinforces the arm’s length principle within the framework of international trade law.